Elderly in Nursing Homes: Between Birr al-Wālidayn Obligations and Social Dynamics In Banten Province - Humaeroh Humaeroh; M.A. Tihami; Ahmad Hidayat; Asep Dadan Suganda; Arifeen Yama (Justicia Islamica, 2025)
The rising trend of placing elderly parents in nursing homes in Banten Province raises questions about its compatibility with Islamic values, particularly the obligation of birr al-wālidayn. This study is grounded in the tension between modern socio-economic demands and religious expectations that children provide direct care for their parents. The objective is to examine this practice through the lens of maqāṣid al-sharī‘ah and assess whether it can still reflect birr al-wālidayn within a changing social context. A qualitative approach was employed, using observations and in-depth interviews with families, nursing home staff, and religious leaders. The analysis draws on credo theory, legal authority theory, social change theory, fatwa evolution theory, and fishbone analysis. Findings indicate that social, economic, and legal factors influence the decision to institutionalize older people. When guided by principles of protection and well-being, such practices can align with Islamic teachings. The study contributes theoretically and practically to developing elderly care policies that are religiously grounded and responsive to contemporary societal dynamics.